(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This comprehensive analysis delves into the concept of numerical inequalities, crucial components of mathematics. It begins by defining numerical inequalities and exploring their properties and solution methods. The article categorizes various types of inequalities, including linear, quadratic, and absolute value inequalities, and discusses their practical applications in fields such as economics and physics.